The role of tumor-associated macrophages in oral squamous cell carcinoma - Xue, Yiwen; Song, Xiao; Fan, Siyu; Deng, Runzhi (Frontiers in Physiology, 2022)
Oral squamous cell carcinoma (OSCC) is a common head and neck cancer with a high recurrence rate and a low 5-year survival rate. Tumor-associated macrophages (TAMs) are important immune cells in the tumor microenvironment, which play an important role in the progression of many tumors. This article reviews the origin, and the role of TAMs in the invasion, metastasis, angiogenesis and immunosuppression of OSCC. Therapeutic strategies targeting TAMs are also discussed in hopes of providing new ideas for the treatment of OSCC.